Evaluasi Tingkat Cacat Produk Menggunakan Six Sigma Pendekatan DMAIC pada UMKM Konveksi X - Amelia Lestari; Amay Suherman; Hanissa Okitasari (Pusat riset dan Inovasi Nasional, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy, including in the garment industry. The subject of this study is MSME X, located in Cimahi City, which specializes in the production of knitted clothing. This research aims to identify production problems, analyze the causes of defects, and design improvement strategies using the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. In the Define stage, the main problems are identified through the Critical to Quality (CTQ) approach, which reveals three major types of defects: button defects (39%), stitching defects (32%), and fabric or pattern defects (29%). Next, the Measure stage is conducted to assess process performance using quality indicators. The calculation results show a Defects per Million Opportunities (DPMO) value of 10,968.95 and a Sigma Level of 3.79, indicating room for improvement. The Analyze stage utilizes Pareto and Fishbone diagrams to identify root causes. The Improve stage applies Failure Mode and Effect Analysis (FMEA) to determine improvement priorities. The Control stage involves the use of Statistical Process Control (SPC), regular inspections, and an incentive system. This approach is expected to reduce defect rates and sustainably improve production efficiency.